Texture image of men's suit fabrics - Chuang, Ming-Chuen; Hung, Shu-Hui (Journal of the Textile Institute, 2011)
In fashion design, form image is the most important factor. Regarding the form image of fashion, texture image is the prime affecting factor. Especially in the case of men's suits, as there is not much variation in their shape and style; therefore, the fabrics used in making them determine their texture image. For this reason, this research probed into the texture image of suit fabrics. First, quality analysis and a comparison of the images of the appearance of a suit were conducted to deduce the consumer's and designer's common understanding of the prototype of a men's suit. Meanwhile, the frequently used fabrics for making men's suit were collected. From them, 61 fabrics were selected as samples for this study. With expert interview and literature review, the morphological chart of the patterns, weave, and color of the fabrics and 16 related adjective pairs of feelings were concluded. Then, the experiments of semantic differential (SD) evaluation on the images of these fabric samples as well as of grouping samples with similar fabric texture were conducted. By factor analysis on the SD evaluation data, an image space with four constituting factors was yielded. By examining the distribution of fabric samples in this space, the relationship between the physical features concerning the texture image and the subject's feeling of the image were concluded. Furthermore, this research has figured out a three-dimensional perceptual space of texture images of suit fabrics through multidimensional scaling (MDS) analysis of the data collected from the similarity grouping experiment. Based on these results, certain principles for the design of texture images for men's suits of proper fabrics were proposed.